Development of an empirical model for surface roughness in the machining of Al/SiC particulate composites by PCD tool. (30th June 2008) - Palanikumar, K.; Sivakumar, G.; Davim, J. Paulo
Silicon carbide reinforced aluminium metal matrix (Al/SiC-MMC) composites are finding increased applications in many engineering fields. Accordingly, the accurate machining is needed for industry. In this paper, an empirical model has been developed to predict the surface roughness in machining of Al/SiC-MMC composites using Poly Crystalline Diamond (PCD) tool. Regression analysis and Analysis of Variance (ANOVA) are used to study the main and interaction effects of machining parameters. The developed model can be effectively used to predict the surface roughness in machining Al/SiC particulate components within the ranges of parameters studied. The influences of different parameters in machining Al/SiC-MMC composites have been analysed in detail.